The Determinants of Mutual Funds Success in Pakistan - Chhapra, Imran Umer; Rehan, Raja; Rafay, Abdul (Faculty of Economic and Business, 2018)
The prime goal of this research is to find out the determinants of mutual fund’s success in Pakistan. This study exploits the convenient sampling techniques and the data gathered from fund manager reports, annual reports, and from CDCPL. The sample size of this study relaxed to six Assets Management Companies (AMC)’s from 2013 to 2017. We applied a unit root test for finding the nature of data and check the variation of variable’s mutual performance by Hausman Technique. Moreover, we depicted the association between dependent and independent variables with the help of Constant Coefficient Model. It was concluded that risk-adjusted return, management structure, and expense ratio have a significant impact on the size of fund of selected AMC’S of Pakistan. However, the net asset value found to be negatively related with the size of the fund. This research will help investors, AMC’s and regulatory bodies to understand the dynamics of mutual funds in Pakistan.DOI: 10.15408/ess.v8i2.7431